Pengaruh Sosial Media Instagram terhadap Keputusan Pembelian Produk Madu Efi (Jurnal Agribisnis dan Agrowisata, 2026)
The Influence of Instagram Social Media on the Purchase Decision of Efi's Honey Products. Efi's garden is one of the businesses that market and promote their products, namely Efi's Honey products through social media, especially Instagram. This study aims to analyze the social media characteristics of Kebun Efi's Instagram and to determine the effect of Instagram social media on purchasing decisions for Madu Efi's products. The sampling technique used was the distribution of accidental sampling questionnaires to every Instagram followers of Kebun Efi who had purchased and consumed Efi's Honey products.From the results of the analysis after being modified so that it was found that on the social media characteristics of Instagram on the communication indicators the remaining parameters were the parameters "content containing efi honey product information" (X2.1) and "use of attractive taglines" (X2.2) meaning that these two parameters is the one that most influences the communication indicator in reflecting the characteristics of Instagram social media while on the collaboration indicator that the parameter "there are direct messages (DM) for questions and information about products" (X3.2) which most influences the collaboration indicator in reflecting the characteristics of Instagram social media. In the connection indicator, all parameters affect these indicators in reflecting the characteristics of social media Instagram. This means that the parameters contained in the connection indicator also most influence the consumer's decision to buy EFI honey products. Social media Instagram has a significant effect on purchasing decisions seen from the t-statistics value of 11.322 and the p-value of 0.000. The advice given is that farm management must always be sensitive to current trend developments and to always look for reference ideas for creating interesting content themes so that they are not monotonous and boring. This is done to maintain consumer interest in buying efi honey products.
Keywords: efi honey; instagram social media; purchase decision